Pass-through of external shocks to euro area inflation - Elke Hahn (European Central Bank (ECB), 2003)
This paper investigates the pass-through of external shocks, i.e. oil price shocks, exchange rate shocks, and non-oil import price shocks to euro area inflation at different stages of distribution (import prices, producer prices and consumer prices). The analysis is based on a VAR model that includes the distribution chain of pricing. According to our results the pass-through is largest and fastest for non-oil import price shocks, followed by exchange rate shocks and oil price shocks. The size and the speed of the pass-through of these shocks decline along the distribution chain. External shocks explain a large fraction of the variance in all price indices. They seem to have contributed largely to inflation in the euro area since the start of the European Monetary Union. The results on the size and the speed of the pass-through in the euro area appeared to be robust over time and different identification schemes.
Keywords: C32; E31; 330; Euro Area Inflation; exchange rate; Import Price; Oil Price; Pass-Through